Treatment planning (14.04.02): electronic course - Sukhikh E. S. Evgeniya Sergeevna; Selikhova E. A. Ekaterina Alexandrovna; Sutygina Y. N. Yana Nikolaevna; Stakhova O. M. Olga Mikhailovna; Sagov I. R. Islam Ruslanovich (Томск, TPU Moodle, 2025)
The objectives of "Treatment Planning" course include the development of students’ knowledge and ideas of modern methods, algorithms and procedures used for calculation/simulation of the radiation dose distribution in patients during radiation therapy (RT). The course also deals with clinical aspects of RT, which include pretreatment procedures based on CT, MRI images, importance and use of immobilization devices, prescription for RT course, dosimetric treatment planning, certain aspect of treatment procedures themselves, Quality Assurance (QA) of radiotherapy equipment and individual treatment plans. The clinical aspects are given for the major malignancies which medical physicists will deal during their career. Students will learn to find the solution of research and applied problems connected with radiotherapy and dosimetric equipment. Special attention during the course is given to practical skills of the application of methods of calculation of dose distribution in the patient's body generated by various sources ionizing radiation and dose delivery techniques; principles of control levels calculating for tumour and damage to healthy tissues and organs at risk; to QA aspects of radiotherapy equipment and individual treatment plans